Teologiczne aspekty błogosławieństwa Symeona (Łk 2, 29-35) - Gryglewicz, Feliks (The Biblical Annals, 2017)
Simeon speaks about God who has unlimited power, caring for the chosen people and deciding everything that concerned Simeon, and above all the Messiah. The Messiah is the saviour who is compared with light, he is also the subject of controversy; the two parts of Simeon’s blessing show us two different aspects of the Messiah: he it is who brings redemption and the teachings coming from God, he is also the cause of spiritual re-birth for many; for others he is the cause of ultimate downfall, especially for those who do not want so unite under his banner or follow him. The person, of the Holy Virgin is one of sorrow, suffering together with Her Son. The theological ideas contained in Simeon’s hymn are near in meaning to what, in the original Church, was represented by John’s tradition.